Break of day [large type] - Coble, Colleen (Coble, Colleen. Annie Pederson novel, 2023)
"Law enforcement officer Annie Pederson's life has been rocked by tragedy, but things finally seem to be heading in the right direction. Her relationship with the love of her life--who's also the biological father of her precious daughter--has never been better, and it looks like an engagement ring is in Annie's future. She's also slowly building back trust with her sister, Sarah, after a separation that lasted for decades. When a man escapes law enforcement custody and Sarah's safety is suddenly in question, Annie's personal and professional lives once again merge. Meanwhile, her investigation of hikers who have gone missing in the remote woods of Michigan's Upper Peninsula puts her in the crosshairs of a deadly game. Now, Annie is the one being hunted. When she discovers the terrible truth about the men who are stalking her, she realizes that she's in for the fight of her life if she's going to redeem the sister she once lost, build the family she dreams of, and keep all those she loves safe" --